2011
DOI: 10.1093/eurheartj/ehr195
|View full text |Cite
|
Sign up to set email alerts
|

Combustion-derived nanoparticulate induces the adverse vascular effects of diesel exhaust inhalation

Abstract: AimExposure to road traffic and air pollution may be a trigger of acute myocardial infarction, but the individual pollutants responsible for this effect have not been established. We assess the role of combustion-derived-nanoparticles in mediating the adverse cardiovascular effects of air pollution.Methods and resultsTo determine the in vivo effects of inhalation of diesel exhaust components, 16 healthy volunteers were exposed to (i) dilute diesel exhaust, (ii) pure carbon nanoparticulate, (iii) filtered diese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
150
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(163 citation statements)
references
References 44 publications
10
150
0
3
Order By: Relevance
“…Observations in healthy young volunteers exposed to pure elemental carbon particles implied that heart function was not affected by these controlled exposures. This was confirmed by a very similar exposure in a study (Mills et al, 2011) that looked at measurements of arterial stiffness and blood clothing in healthy subjects. The presence of a susceptible population has not been shown, and no studies could be identified that have applied exposure periods longer than 2 hours.…”
Section: Clinical Studiessupporting
confidence: 61%
See 3 more Smart Citations
“…Observations in healthy young volunteers exposed to pure elemental carbon particles implied that heart function was not affected by these controlled exposures. This was confirmed by a very similar exposure in a study (Mills et al, 2011) that looked at measurements of arterial stiffness and blood clothing in healthy subjects. The presence of a susceptible population has not been shown, and no studies could be identified that have applied exposure periods longer than 2 hours.…”
Section: Clinical Studiessupporting
confidence: 61%
“…The effects of ultrafine carbon particles were observed in both heart rate variability and cardiac repolarization, but there were no changes in soluble markers of either systemic inflammation or coagulation. In a more recent study, no vascular impairment or effect on blood clotting were observed in volunteers exposed for 2 hours to 70 µg/m 3 of ultrafine carbon particles (Mills et al, 2011). In this same study, and in Lucking et al (2011), it was shown that removing the particles from diluted diesel engine exhaust also prevented adverse effects on the cardiovascular system.…”
Section: Clinical Studiesmentioning
confidence: 56%
See 2 more Smart Citations
“…The authors are not aware of any published human inhalation studies using iron oxide nanoparticles. However, several controlled human inhalation studies have exposed volunteers to other ultrafine particles [57][58][59][60][61][62][63][64][65][66]. In addition, many human inhalation studies have been conducted using Technegas or 99m Tc labeled ultrafine carbon particles; however, this literature is beyond the scope of this review.…”
Section: Controlled Human Volunteer Inhalation Studiesmentioning
confidence: 99%